Lack of phenotypic plasticity in leaf hydraulics for 10 woody species common to urban forests of North China. (17th January 2022) - Han, Hang; Xi, Benye; Wang, Ye; Feng, Jinchao; Li, Ximeng; Tissue, David T
Abstract: The survival and performance of urban forests are increasingly challenged by urban drought, consequently compromising the sustainability and functionality of urban vegetation. Plant–water relations largely determine species drought tolerance, yet little is known about the hydraulics of urban forest species. Here, we report the leaf hydraulic and carbon traits that govern plant growth and drought resistance, including vulnerability to embolism, hydraulic conductivity and leaf gas exchange characteristics, as well as morphological traits that are potentially linked with these physiological attributes, with the aim of guiding species selection and management in urban forests. Plant materials were collected from mature shrubs and trees on our university campus in Beijing, representing 10 woody species common to urban forests in north China. We found that the leaf embolism resistance, represented by the water potential inducing 50% loss of hydraulic conductivity ( P 50 ), as well as the hydraulic safety margin (HSM) defined by P 50 and the water potential threshold at the inception of embolism ( P 12 ), varied remarkably across species, but was unrelated to growth form. Likewise, stem and leaf-specific hydraulic conductivity ( K stem and k l ) was also highly species-specific. Leaf P 50 was positively correlated with hydraulic conductivity. However, neither P 50 nor hydraulic conductivity was correlated with leaf gas exchange traits, including maximum photosynthetic rate ( A max ) and stomatal conductance ( g s ). Plant morphological and physiological traits were not related, except for specific leaf area, which showed a negative relationship with HSM. Traits influencing plant–water transport were primarily correlated with the mean annual precipitation of species climatic niche. Overall, current common woody species in urban forest environments differed widely in their drought resistance and did not have the capacity to modify these characteristics in response to a changing climate. Species morphology provides limited information regarding physiological drought resistance. Thus, screening urban forest species based on plant physiology is essential to sustain the ecological services of urban forests.